The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1051/0004-6361:20031318
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of small to large separations of acoustic oscillations as a diagnostic of the interior of solar-like stars

Abstract: Abstract.By considering stellar models with the same interior structure but different outer layers we demonstrate that the ratio of the small to large separations of acoustic oscillations in solar-like stars is essentially independent of the structure of the outer layers, and is determined solely by the interior structure. Defining the scaled Eulerian pressure perturbation ψ (ω, t) = rp /(ρc) 1/2 we define the internal phase shift δ (ω, t) through the relation ωψ/(dψ/dt) = tan(ωt − π /2 + δ ). The δ are almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
355
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(359 citation statements)
references
References 11 publications
3
355
1
Order By: Relevance
“…On the other hand Creevey and to some extent Verma are less sensitive to the surface frequency correction because of the use of frequency separations and ratios. For these latter, the lack of sensitivity was explained by Roxburgh & Vorontsov (2003b). The additional regularisation parameters of Verma may also contribute to a different χ 2 .…”
Section: Analysis Of Model Differencesmentioning
confidence: 99%
“…On the other hand Creevey and to some extent Verma are less sensitive to the surface frequency correction because of the use of frequency separations and ratios. For these latter, the lack of sensitivity was explained by Roxburgh & Vorontsov (2003b). The additional regularisation parameters of Verma may also contribute to a different χ 2 .…”
Section: Analysis Of Model Differencesmentioning
confidence: 99%
“…In these cases, instead of fitting for the global asteroseismic parameters the Bayesian schemes aim at reproducing either the individual frequencies of oscillations or combinations of them. The first approach usually relies on an empirical surface correction to account for incomplete modelling of the outer stellar layers in 1-D hydrostatic codes (e.g., Kjeldsen et al 2008), while the latter suppresses the influence of these layers by building frequency rations (Roxburgh & Vorontsov 2003). Recently Lebreton & Goupil (2014) showed that the most precise asterosesimic ages for dwarfs are those obtained using the frequency ratios as fitting observables as they are sensitive to the innermost layers of the star.…”
Section: Improvements For Dwarfs and Subgiants: Individual Frequenciesmentioning
confidence: 99%
“…Roxburgh & Vorontsov (2003) have demonstrated that the ratio of the small to large separations of acoustic oscillations is essentially independent of the structure of the outer layers. We thus renormalize the small spacings by considering the ratios δν 02 (n)/∆ν(n, ℓ = 1), δν 13 (n)/∆ν(n + 1, ℓ = 0) and δν 01 (n)/∆ν(n, ℓ = 1) where the large separation is given by:…”
Section: Fig 4 Relative Frequency Differences Between the Gravity Mmentioning
confidence: 99%